Enantioselective Regulation of Lactate Racemization by LarR in Lactobacillus plantarum - Desguin, Benoît (J Bacteriol, 2014)
Lactobacillus plantarum is a lactic acid bacterium that produces a racemic mixture of l- and d-lactate from sugar fermentation. The interconversion of lactate isomers is performed by a lactate racemase (Lar) that is transcriptionally controlled by the l-/d-lactate ratio and maximally induced in the presence of l-lactate. We previously reported that the Lar activity depends on the expression of two divergently oriented operons: (i) the larABCDE operon encodes the nickel-dependent lactate racemase (LarA), its maturases (LarBCE), and a lactic acid channel (LarD), and (ii) the larR(MN)QO operon encodes a transcriptional regulator (LarR) and a four-component ABC-type nickel transporter [Lar(MN), in which the M and N components are fused, LarQ, and LarO]. LarR is a novel regulator of the Crp-Fnr family (PrfA group). Here, the role of LarR was further characterized in vivo and in vitro. We show that LarR is a positive regulator that is absolutely required for the expression of Lar activity. Using gel retardation experiments, we demonstrate that LarR binds to a 16-bp palindromic sequence (Lar box motif) that is present in the larR-larA intergenic region. Mutations in the Lar box strongly affect LarR binding and completely abolish transcription from the larA promoter (P(larA)). Two half-Lar boxes located between the Lar box and the −35 box of P(larA) promote LarR multimerization on DNA, and point mutations within one or both half-Lar boxes inhibit P(larA) induction by l-lactate. Gel retardation and footprinting experiments indicate that l-lactate has a positive effect on the binding and multimerization of LarR, while d-lactate antagonizes the positive effect of l-lactate. A possible mechanism of LarR regulation by lactate enantiomers is proposed.